A Picture Speaks a Thousand Words: Crisis Communication and Image Making of Indonesian Public Leaders on Instagram - Dewa Ayu Diah Angendari (Ikatan Sarjana Komunikasi Indonesia, 2022)
During crisis, such as Covid-19 pandemic, public leaders are expected to be able to provide information that explains the situation at hand to the affected public while at the same time giving psychologically comforting messages. Nevertheless, a crisis can also be seen as a political event. Political actors use crisis as a momentum to change policies, gain support, and strengthen their positiveimage by showing off their capabilities in handling crisis. The absence of media gatekeeper in digital realms provides wider opportunities for political actors to set their agenda. Previous research found that Instagram is an effective medium to disseminate health-related messages and provides a platform for political actors to engage with their followers. Hence, this study seeks to understand how public leaders communicate crisis on Instagram. This research uses content analysis method by taking data from the Instagram of four prominent public leaders in Indonesia during the period from February 29 to May 29 2020. Findings show that all the four public leaders are actively uploading social media content during the beginning of the pandemic, focusing on showcasing their efforts to fight the virus, demonstrating leadership, proximity, and intimacy towards their followers. This study contributes to the study of crisis communication by providing understanding about the use of crisis as an image-making momentum in social media by public leaders.